Crx Is Posttranscriptionally Regulated by Light Stimulation in Postnatal Rat Retina - Wu, Yihui; Qiu, Jin; Chen, Shuilian; Chen, Xi; Zhang, Jing; Zhuang, Jiejie; Liu, Sian; Yang, Meng; Zhou, Pan; Chen, Haoting; Ge, Jian; Yu, Keming; et al. (Frontiers in Cell and Developmental Biology, 2020)
Abstract Cone rod homeobox (Crx) plays a key role at the center of a regulatory network that coordinates many pathways in the retina. Its abnormal expression induces retinal disorders. However, the underlying regulatory mechanism of Crx expression is not well defined. Here, our data showed that the levels of Crx mRNA at 24 hours and 48 hours were consistent with that of Crx protein in primary retinal neurocytes cultured in both complete darkness (D/D) and on a daily light-dark cycle (L/D). However, Crx protein levels were significantly higher (2.56-fold) in cells cultured in the dark than in cells cultured in light, whereas Crx mRNA was not changed in either type of cell. Moreover, the level of Crx protein in retinal neurocytes showed a light intensity-dependent decrease. The expression patterns of downstream genes, rhodopsin and arrestin, also supported these results. Furthermore, a Crx promoter activity assay performed in primary retinal neurocytes also indicated that light exposure and darkness did not affect its inducibility. The inconsistency between Crx mRNA and protein expression was specific to the endogenous Crx gene. The protein level of exogenous Crx in 661W cells cultured in the dark was the same as the protein level of Crx in cells cultured in light by the transfection of a plasmid containing Crx cDNA. More importantly, this observation was confirmed in vivo in postnatal day 15 (P15) retinas but not in adult retinas. Therefore, our study revealed a mechanism by which Crx is posttranscriptionally regulated by light stimulation in postnatal rat retina.